Odpowiedzi

2010-02-21T14:31:28+01:00
2√3 = pod pierwiastkiem 2*2*3 = pod pierwiastkiem 12

3√2 = 3*3*2=18

4√3 = 4*4*3=48

5√2 = 5*5*2=50

6√3 = 6*6*3=108

2³√2 = 2*2*2*2=16

3³√2 = 3*3*3*2=54

4³√2 = 4*4*4*2=128

5³√2 = 5*5*5*2=250

6³√2 = 6*6*6*2=432

Pmiętaj, że to moje po równa się ma być pod pierwiatkiem :)
Najlepsza Odpowiedź!
2010-02-21T14:33:03+01:00
2√3=√3*2²=√3*4=√12
3√2=√2*3²=√2*9=√18
4√3=√3*4²=√3*16=√48
5√2=√2*5²=√2*25=√50
6√3=√3*6²=√3*36=√108
2³√2=³√2*2³=³√2*8=³√16
3³√2=³√2*3³=³√2*27=³√54
4³√2=³√2*4³=³√2*64=³√128
5³√2=³√2*5³=³√2*125=³√250
6³√2=³√2*6³=³√2*216=³√432
2010-02-21T14:34:28+01:00
2√3= √4 × √3 = √ 12
3√2 = √9 × √2 = √18
4√3= √ 16 × √3 = √64
5√2= √25 × √2 = √50
6√3=√36 × √3 = √108
2³√2= ∛ 8 × ∛2 = ∛16
3³√2= ∛27× ∛2 = ∛54
4³√2= ∛64 × √2 = ∛128
5³√2= ∛125 × ∛2 = ∛ 250
6³√2= ∛ 216 × ∛ 2 = ∛432